Mekanisme Koping Ibu Yang Mengalami Postpartum Blues - Silvrida - Silalaen; Misrawati - -; Sofiana - Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
Postpartum blues arises when a mother failed to accept their condition caused of pregnancy, pregnancy process ,delivery and post partum. This research is highly essential since postpartum blues which is known as a form of a light depression,can develop into postpartum depression if it is not well handled.This research is aimed to explore coping mechanism who has postpartum blues by using qualitative research methodwithPhenomenology approach. Four participants which are chosen by purposive sampling technique have experienced data saturation from local State hospital Arifin Achmad Pekanbaru. Data is gathered through interview (In depth interview), field record, the input result of The Edinburgh Postnatal Depression Scale (EPDS) andanalyzed by using Colaizzi method. the result of the research identifies two theme, they are coping mechanism and coping impact which are used. Coping mechanism which is used is by the participant namely coping and maladaptive mechanism and the impact coping which is used namely positive and negative impact. The result of this research suggests the nurses to give more attention to the psychological health of a mother after delivery by giving support therapyby doing so, it will show emotional concerns, appreciations, and informations or by giving nursery aid to the mother after delivery. Keywords:coping mechanism, postpartum blues